2014
DOI: 10.14737/journal.aavs/2014/2.8.447.456
|View full text |Cite
|
Sign up to set email alerts
|

Proteases and Proteases Inhibitors of Semen - A Review

Abstract: | The ejaculate composition is extremely complicated and variable among livestock species. The seminal proteins and enzymes are vital for ejaculate metabolism, spermatozoa performance, survival, and transport within the feminine reproductive tract. Proteases and proteinase inhibitors are secreted by the accessory sex glands of the male reproductive tract and find mixed with the spermatozoa throughout ejaculation. But an entire understanding of those enzymes and their performance in numerous class species is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…Zahn et al [46] stated that the protein with a MW of about 53-55 kDa is proacrosin. Gurupriya et al [47] stated that proacrosin is found in the acrosome. When the sperm acrosome is damaged, or there is early capacitation at the time of freeze-thawing, it can stimulate the premature transformation of proacrosin into the enzymatic protein called acrosin.…”
Section: The Analysis Of Sperm Protein By Sds-pagementioning
confidence: 99%
“…Zahn et al [46] stated that the protein with a MW of about 53-55 kDa is proacrosin. Gurupriya et al [47] stated that proacrosin is found in the acrosome. When the sperm acrosome is damaged, or there is early capacitation at the time of freeze-thawing, it can stimulate the premature transformation of proacrosin into the enzymatic protein called acrosin.…”
Section: The Analysis Of Sperm Protein By Sds-pagementioning
confidence: 99%
“…Proteomics profiles reflect sperm functional traits (Intasqui et al, ) and highly differ between species. A significant number of seminal proteases and protease inhibitors are suspected to participate in the regulation of maturation/activation, release, and protection of sperm (Cesari, Monclus Mde, Tejon, Clementi, & Fornes, ; Gurupriya et al, ; Laflamme & Wolfner, ). In many species, acrosin is an essential trypsin‐like serine protease stored in the sperm acrosome as an inactive zymogen form, proacrosin, before its activation by limited proteolysis that releases the active acrosin at the time of fertilization (Bozzola et al, ; Slowinska, Olczak, Liszewska, Watorek, & Ciereszko, ).…”
Section: Introductionmentioning
confidence: 99%
“…Denaturation of proteins during cryopreservation results in the leakage of protease from the lysosomes found in the acrosome leading to loss of membrane integrity (32). During cryopreservation, some proteases and protease inhibitors are prematurely activated; thus, natural proteolysis regulation in cryopreserved semen is compromised (33). This may also be due to the heterogenicity of seminal plasma and sperm in the mammalian ejaculate (34) The protein changes in sperm may also be due to the difference in their responsiveness to seminal plasma (35).…”
Section: Discussionmentioning
confidence: 99%